An estimation of economic models with recursive preferences - Xiaohong Chen; Jack Favilukis; Sydney C. Ludvigson (Centre for Microdata Methods and Practice (cemmap), 2012)
This paper presents estimates of key preference parameters of the Epstein and Zin (1989, 1991) and Weil (1989) (EZW) recursive utility model, evaluates the model's ability to fit asset return data relative to other asset pricing models, and investigates the implications of such estimates for the unobservable aggregate wealth return. Our empirical results indicate that the estimated relative risk aversion parameter ranges from 17-60, with higher values for aggregate consumption than for stockholder consumption, while the estimated elasticity of intertemporal substitution is above one. In addition, the estimated model-implied aggregate wealth return is found to be weakly correlated with the CRSP value-weighted stock market return, suggesting that the return to human wealth is negatively correlated with the aggregate stock market return.
Keywords: G12; E21; 330